The Transmission of a Religious Heritage to Younger Members of Small Ethnic Communities in a Pluralist Society: The Perceptions of Young Australian Copts - De Souza, Marian (Journal for the academic study of religion, 2004)
Contemporary Australia has clearly become a multi-faith and multi-cultural society. Even within the mainstream Christian religions there are many new arrivals whose countries of origin are non Euro-centric, and they have brought with them a wide variety of cultural practices that are different from the Anglo-Saxon/Celtic culture that has dominated religious practice in this country. Consequently, the ‘face’ of Australian Christians has been slowly changing. In particular, young Australians have been exposed to a wide range of cultural and religious practices through both community interaction and a highly influential media. Within this framework, the Copts are a small growing ethnic community who are focused on handing on their cultural and religious heritage to their younger members. This paper will explore the transmission of the Coptic religious heritage, and discuss what some school-going Copts say about the various influences on their religiosity and spirituality.